Heal yourself with traditional Chinese medicine find relief from chronic pain, stress, hormonal issues and more with natural practices and ancient knowledge - Choi, Lily; Koutroumanis, Bess (Salem, MA Page Street Publishing Co, 2023)
"If you've experienced chronic health issues and felt Western medicine didn't lead to a lasting cure, let this book set you on the path of healing. Traditional Chinese Medicine (TCM) is an ancient school of thought that has treated illness and disease for centuries, with proven results. This holistic practice uses natural remedies and insightful wisdoms about how the body works to target illness at the root cause and cure it for good. Dr. Lily Choi, a top practitioner and leading voice in TCM, breaks down how this medicinal practice works, and teaches you how to implement effective TCM methods right in your own home. You'll use natural modalities like acupressure, herbalism and meditation to improve your symptoms and free yourself of the cycle of sickness and prescriptions. This book provides detailed treatments for an array of conditions, such as headaches and migraines, hair loss, insomnia, infertility, constipation, anxiety, arthritis, tinnitus and so much more. For every ailment covered, Dr. Lily prescribes food and herbs, acupressure regiments and lifestyle changes that all help eliminate and solve each issue. And as you read, TCM concepts like our life force, Qi, and the balance of Yin and Yang within us will not only begin to make sense, but help you foster a deeper, truer connection to your body, mind and spirit. Get ready to take control of your health and find lasting relief with these powerful, natural practices"--Publisher's description.
Includes index.
113262
Keywords: Medicine, Chinese; Medicine, Chinese -- Popular works; Self-care, Health -- Popular works; Medicine, Chinese Traditional; Popular works